Contested welfare states : welfare attitudes in Europe and beyond - Svallfors, Stefan (Studies in social inequality., 2012)
This book analyses people's attitudes toward welfare policies across Europe, and offers a novel comparison with the United States. Occupied with normative orientations toward the redistribution of resources and public policies aimed at ameliorating adverse conditions, the book focusses on the interplay between individual welfare attitudes and behaviour, institutional contexts, and structural variables. It provides essential input into the comparative study of welfare state attitudes and offers critical insights into the public legitimacy of welfare state reform.